OPTIMALKAN PENGELOLAAN KEUANGAN: PELATIHAN EFEKTIF REKONSILIASI BANK DAN KAS UNTUK GURU - Ayu Aulia Oktaviani; Herawaty, Vinola; Daeli, Florus; Puspitasari, Windhy; Sitinjak, Gold Naro (LPPM Universitas Al Muslim, 2024)
Good financial management is very important for the smooth operations of educational institutions. Teachers as fund managers play an important role in ensuring transparency and accountability of school finances, especially bank and cash reconciliation practices. However, many teachers do not yet have an understanding of this procedure, resulting in discrepancies in school financial management. This activity aimed to provide training to the teachers on how to carry out bank and cash reconciliation effectively. The method of implementing activities was in the form of counseling and training delivered by a team of lecturers from the Faculty of Economics and Business, Trisakti University. The training material covered skills, knowledge and work attitudes in managing cash fund documents and bank reconciliation. The training was held in December 2023 at the Trisakti University Campus, attended by 22 teachers in West Jakarta. The community service activity results showed that five participants who took the competency test demonstrated their competence and confirmed the effectiveness of training methods involving interactive discussions, practical demonstrations and the use of technology. Thus, it is effective in increasing teachers' understanding and skills in managing school finances in a transparent and accountable manner. These results indicate the need to expand the scope of training to more teachers and the importance of collaborative approaches and the use of technology to develop capacity in the field of education.